Improving Competence and Confidence With Evidence-Based Practice Among Nurses: Outcomes of a Quality Improvement Project. Issue 5 (September 2016) - Bissett, Kim M.; Cvach, Maria; White, Kathleen M.
Abstract : Evidence-based practice (EBP) is an integral part of quality patient care, reduction in practice variation, and increased nursing autonomy. Yet, EBP is not a consistent standard in many organizations. Although many barriers to EBP have been cited, this project focused on poor knowledge of the EBP process and a lack of available EBP mentors or experts. A bundled set of educational interventions to improve the EBP confidence and self-efficacy of nurses was developed and implemented. Comparison of pre/post data showed improvement in all categories and questions. Committee members expressed greater confidence with the process and comfort level with leading EBP projects following the intervention. The educational bundle used in this project can serve as a model for others looking to develop competent EBP mentors within their organization.